Feasibility of silicon nanoparticles produced by fast-rate plasma spray PVD for high density lithium-ion storage. (21st September 2021) - Ohta, R; Tanaka, T; Takeuchi, A; Dougakiuchi, M; Fukuda, K; Kambara, M
Abstract: Si nanoparticles with the averaged primary particle size ranging from 20 to 175 nm have been produced by plasma spray physical vapor deposition (PS-PVD) at different powder feed rates from 0.6 to 25.4 g min −1 . High-order agglomerates as large as 10 µ m are found to form especially at low powder feed rate, while such large agglomerates are suppressed when the particle size becomes greater than 100 nm at high powder feed rate. The electrochemical cells using Si nanoparticles smaller than 100 nm retain relatively high capacity with reasonable cycle stability, while the capacity drops rapidly for the cells with Si greater than 100 nm due partly to an increased charge transfer resistance. Moreover, ultrasonic particle breakup reveals that absence of large agglomerates as large as 10 µ m are beneficial in reducing the charge-transfer resistance and in improving the cycle stability. Although oxygen content increases with decreasing the particle size, slow oxidation upon collection of the particles after PS-PVD successfully suppresses excessive oxidation, leading to negligible influence on the initial efficiency.